THE RELATIONSHIP BETWEEN SEAGRASS Thalassia hemprichii PERCENTAGE COVER AND THEIR BIOMASS - Mallombasi, Andi; Mashoreng, Supriadi; La Nafie, Yayu A. (Jurnal Ilmu Kelautan SPERMONDE, 2020)
Seagrass has many functions and values, including as carbon sink. However, to estimate carbon in seagrass, it involves seagrass biomass harvesting which is laborious, costly, and destructive. This study aimed to find out the relationship between seagrass Thalassia hemprichii percent cover with their biomass which will provide alternative method for biomass estimation leading to an efficient, less cost and less destructive method for seagrass carbon stock estimation. Seagrass were sampled in Bonebatang island, South Sulawesi, and estimated their percent cover following SeagrassWatch Method from different seagrass condition and sediment type, as well as harvested for their biomass. In the lab, seagrass biomass was dried. Data was analyzed by using simple regression analysis. Results showed that there is a relatively strong relationship between percent cover and the belowground, aboveground and total biomass (R2 = 0.70; 0,81 and 8,3, respectively). Seagrass percent cover (seagrass health status, i.e. healthy, moderate and poor) also resulted a relatively strong influence on total seagrass biomass (R2>50%). However, apart from segarss percent cover, some other parameters are needed to be taken into consideration, such as seagrass densities and seagrass morphologies